Financial Inclusion in Romania – A New Perspective - Alina Elena Cerchia (Ionașcu); Elena Cerasela Spătariu; Gabriela Gheorghiu (Ovidius University Annals: Economic Sciences Series, 2022)
Financial inclusion is an important national subject, sustained by the European Union policies. Financial inclusion has an outstanding role in growing the quality of life of citizen, and financial inclusion can be accomplished both through educational programs and through programs which facilitate access to financial products and services. The financial inclusion score, a very useful instrument, can be influenced by many factors in order to decrease the major gap between the urban and rural environment. In this paper, we analyze the level of financial education and inclusion of Romanians, the barriers that are encountered and giving solutions to enhance the level of financial inclusion in Romania. The low levels of financial inclusion can be improved by the government through public polices mainly, but also in partnership with banks or other non-governmental institutions, regarding digitalization, financial education and fiscal and non-fiscal policies.